study of ginsenoside on PPARγ expression of mononuclear macrophage in type 2 diabetes - Ni, Hai-xiang; Yu, Ning-juan; Yang, Xue-hui (Molecular biology reports, 2010)
Peroxisome proliferator-activated receptors (PPARs) are transcriptional factors, which play a key role in modulating glucose and lipid metabolism and in the pathogenesis of atherosclerosis. Ginsenosides are the active components of ginseng, which is a perennial aromatic herb that is widely used in China for medicinal purposes. Some studies have reported that ginsenosides have anti-hyperglycemia and anti-obesity effects that involve the PPAR-mediated pathway. The aims of this study were to investigate mononuclear macrophage PPARγ mRNA expression of type 2 diabetes and the effect of ginsenosides on PPARγ mRNA expression and glucose and lipid metabolism. Our results showed that subjects with type 2 diabetes had lower PPARγ mRNA levels compared with normal controls. Following 2 weeks of 41 mg/day ginsenoside treatment, the expression of PPARγ mRNA in patients with type 2 diabetes was significantly increased, the total cholesterol and triglyceride levels were significantly decreased, and the blood glucose level also decreased (but without statistical significance) compared to the control group. These results demonstrated that ginsenosides improved PPARγ expression and lipid metabolism. Thus, ginsenosides may be applied as an adjuvant for treating type 2 diabetes.